Penataan Ruang Aceh Berbasis Islam dalam Negara Kesatuan Republik Indonesia - Arnita; Fikri (Jurnal Transformasi Administrasi, 2022)
The Helsinki MoU agreement gave birth to Law Number 11 of 2006 concerning the Government of Aceh. In Article 171 Paragraph (1) of Law Number 11 of 2006 it states, "The Aceh Government and district/city Governments have the authority to determine land allotment/spatial use for development purposes guided by statutory regulations." spatial use of Aceh directs spatial use of Aceh in a harmonious, balanced, integrated, sustainable and environmentally sound manner and is based on the philosophy of life and cultural wisdom of the Acehnese people. The philosophy of life and cultural wisdom of the people of Aceh are inseparable from Islamic values. Privileges are special powers to carry out religious life, custom, education, and the role of the clergy in establishing regional policies. Therefore, the field of spatial planning in Aceh can be based on Islamic values. According to Islam, spatial planning in the environment is to improve the welfare of the people, maintain environmental sustainability and harmony, which has a strong nuance of Islamic values. Spatial planning seeks to provide efficiency and improve the quality of life, because the human task is to prosper the earth (land) of Allah SWT, not to destroy it. This research approach is a normative juridical approach or also known as a doctrinal approach or normative legal research. Legal research data sources can be in the form of primary legal materials, secondary legal materials, and non-legal materials. Data collection techniques through a statutory approach. After the existence of the Aceh Qanun concerning the 2013-2033 RTRWA, the Aceh spatial planning no longer revives the mukim mosque and meunasah as the center of community activities. However, the Aceh Province has introduced Islamic values ​​in spatial planning through Asmaul Husna pamphlets along roads in North Aceh and East Aceh, as well as around the fence of the Aceh Governor's Hall. Likewise with the existence of prayer rooms in every hotel and shopping center. Naming the names of Government Agencies and Shops with Jajo Arabic script. Even though Aceh's spatial planning is not strictly based on Islamic values, for example gyms such as gyms do not yet show Islamic values, that is, men and women are still mixed. As well as in shopping centers there are no special places for women to breastfeed. Through the revision of the Aceh RTRW which can be done once every five years, so that later a truly Islamic-based spatial planning is realized, this is so that it is in accordance with the vision and mission of the Aceh RTRW to create prosperous Acehnese people in accordance with the needs and lives of the Acehnese people.